Lisinopril as a prophylactic agent for migraine: a randomised double blind placebo controlled cross over prospective study in Kashmir - Wani, Irfan Yousuf; Saleem, Sheikh; Mehraj, Iqra (International Journal of Advances in Medicine, 2021)
Background: Migraine is one of the commonest neurological disorder seen by neurologists. Many different medications are available to be used as prophylactic agent. We conducted this study to determine the efficacy of Lisinopril as a prophylactic drug for migraine in our region. Methods: Our study is a randomised double blind, placebo controlled, cross over, prospective study. 60 patients were included in this study. Treatment period of 12 weeks with one 10 mg lisinopril tablet once daily for one week then two 10 mg lisinopril tablets once daily for 11 weeks, followed by a two week wash out period. Second treatment period of one placebo tablet once daily for one week and then two placebo tablets for 11 weeks. Thirty participants followed this schedule, and 30 received placebo followed by lisinopril. Primary end points were number of hours with headache, number of days with headache, number of days with migraine. Results: Statistical analysis of data from 41 patients that completed this study revealed that hours with headache, days with headache, days with migraine, and headache severity index were significantly reduced by 16%, 16% , 23% and 17% , respectively, with lisinopril as compared to placebo. Conclusions: This study favours lisinopril as an effective prophylactic drug for migraine. The adverse effects of lisinopril, though of significant frequency, have been mild to moderate in severity but were well tolerated by even normotensive subjects.